The Symptoms and prophylaxis of venous thromboembolism in the population of cancer and hospice patients-what is known? - Składanek, Justyna; Leśkiewicz, Michał; Daniel, Piotr; Otręba, Karina; Cieszkowska, Joanna; Czupryńska, Karolina (Journal of Education, Health and Sport, 2024)
In a group of palliative patients, venous thromboembolism (VTE) is a significant cause of death and reduction in quality of life. Current guidelines and scientific research on thromboprophylaxis most often refer to the population of oncology patients, who differ in many aspects from patients receiving palliative care. Thus, doctors working with patients undergoing palliative treatment have to face many problems related to safety and effectiveness of antithrombotic therapy in this type of care. In the case of chronically ill patients, diagnostic process may be somewhat difficult because the symptoms resulting from the underlying diseases can mask VTE symptoms. The aim of this article is to review the literature on symptoms and thromboprophylaxis in this group of patients. According to the latest guidelines of the American Society of Clinical Oncology (ASCO), it is not recommended to use VTE prophylaxis in outpatient oncology patients routinely, but it should be considered in high-risk patients who received a Khorana score of at least 2 before starting a new chemotherapy cycle. In patients diagnosed with VTE, in long-term prophylaxis lasting at least 6 months, due to greater effectiveness, it is recommended to use low-molecular-weight heparins, edoxaban, rivaroxaban or apixaban instead of vitamin K antagonists, which can be used if the previously mentioned drugs are unavailable. There are some studies which show that thromboprophylaxis may be beneficial for patients in palliative care. On the other hand, another studies’ results suggest that patients won’t gain any benefit from prevention. As our article shows it is very crucial to conduct scientific research on palliative patients and create clear guidelines for prophylaxis for this group of people.